2021
DOI: 10.1007/s00449-021-02605-8
|View full text |Cite|
|
Sign up to set email alerts
|

Anthocyanin extract from Lycium ruthenicum enhanced production of biomass and polysaccharides during submerged fermentation of Agaricus bitorquis (Quél.) Sacc. Chaidam

Abstract: Agaricus bitorquis (Quél.) Sacc. Chaidam (ABSC) is a wild edible fungus uniquely found in the Tibet Plateau. ABSC is rich in polysaccharides that are considered biologically active. This study aimed to determine the feasibility of enhancing exopolysaccharide (EPS) production by ABSC in shake flask culture by supplementing the fermentation medium with anthocyanin extract. Different concentrations of Lycium ruthenicum Murr. (LRM) anthocyanin crude extract were tested on ABSC fermentation. The activity of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Sacc (ABSC), amplifying biomass and polysaccharide production [80]. Wu S. et al [81] found that using LRM anthocyanins as an inducer notably influenced the liquid fermentation of ABSC in large mushrooms, positively impacting ABSC extracellular polysaccharide (EPS) production and mycelial biomass during fermentation.…”
Section: Product Development Of Plant Growth Regulatorsmentioning
confidence: 99%
“…Sacc (ABSC), amplifying biomass and polysaccharide production [80]. Wu S. et al [81] found that using LRM anthocyanins as an inducer notably influenced the liquid fermentation of ABSC in large mushrooms, positively impacting ABSC extracellular polysaccharide (EPS) production and mycelial biomass during fermentation.…”
Section: Product Development Of Plant Growth Regulatorsmentioning
confidence: 99%